EXPLORING THE TOURIST ATTRACTIVENESS OF CULTURAL SITES: THE CASE OF KAZAKHSTAN - Dinara KADYRBEKOVA; Aza YEVLOYEVA; Albina BEIKITOVA; Yerkegul DYUSSEKEYEVA; Bakyt AKTYMBAYEVA; Adil MOLDAGALIYEV; Yerlan ISSAKOV; Lóránt Dénes DÁVID* (Geo Journal of Tourism and Geosites)
The article examines the components contributing to the tourist appeal of cultural sites in the Republic of Kazakhstan, exploring the intricate relationship between their attractiveness and cultural significance. This is vital for promoting sustainable tourism, fostering cultural exchange, and preserving shared cultural heritage for future generations. Understanding what makes a place attractive to tourists is crucial for destination marketing, sustainable tourism planning, and revenue generation. The study was conducted in the context of the search for ways to popularize cultural heritage in domestic tourism. Fifteen distinct variables were identified to delineate the allure of these sites, encompassing criteria such as historical significance, aesthetic and architectural value, integration of a cultural object with the natural landscape and environment, involvement of the local community in the promotion and preservation of cultural heritage, among others. A comprehensive questionnaire was devised based on these variables, serving as the foundation for a survey where participants rated the significance of each variable on a 5-point scale. The survey garnered responses from 1,728 residents spanning all regions of Kazakhstan. Through correlation analysis, the acquired ratings were scrutinized, unveiling interconnections among variables and elucidating the primary factors shaping the attractiveness of cultural sites, namely safety and security at the site, the historical significance, accessibility for people with special needs, aesthetic and architectural value, as well as the availability of amenities such as restrooms, information centers, and guided tours.